Evaluation of the Safety and Immunogenicity of Duck-Plague Virus gE Mutants - Yaru Ning (Frontiers in Immunology, 2022)
Duck plague (DP) is an acute infectious disease in the duck industry. The duck plague virus (DPV) is the pathogen, a subfamily of alphaherpesvirinae. gE is a type I membrane protein that contains three parts: an extracellular domain, a transmembrane domain, and a cytoplasmic domain. gE is the major virulence determinant of α-herpesvirus. However, the functions of the gE extracellular and cytoplasmic domains have not been reported in DPV. In this study, a gE extracellular domain deletion mutant and a gE cytoplasmic domain deletion mutant were constructed from DPV. Virus replication kinetics showed that the growth titers of both the gE ectodomain-deleted mutant virus and the gE cytoplasmic domain-deleted virus in DEFs were lower than that of the parental virus CHv-50. DPV CHv-gEΔET and DPV CHv-gEΔCT were continuously passed to the 20th passage in DEFs and the 10th in ducklings. The mutant virus DNA after passage was extracted for identification. The results showed that the gE ectodomain and gE cytoplasmic domain deletion mutant viruses have good genetic stability. The ducklings in each group (n=10) were inoculated with the same titers of DPV CHv-gEΔET, DPV CHv-gEΔCT, DPV CHv-ΔgE, and parental CHv-50, respectively. Clinical symptoms and serum antibody levels were detected after inoculation. The results showed that the virulence of DPV CHv-gEΔCT to ducklings was reduced compared with parental CHv-50, while the virulence of DPV CHv-gEΔET to ducklings was significantly reduced. 105 TCID50 DPV CHv-gEΔET or DPV CHv-ΔgE can induce ducklings to produce DPV-specific antibodies, protect the ducklings from virulent CHv challenge. Therefore, DPV CHv-gEΔET may serve as a promising vaccine candidate to prevent and control duck plague.